2014
DOI: 10.1177/0733464814541325
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Rehabilitation Outcomes in a National Sample of Medicare Beneficiaries With Hip Fracture

Abstract: Effects of patient characteristics on rehabilitation outcomes (functional status at discharge, discharged home) were assessed in a retrospective study of Medicare beneficiaries admitted to inpatient rehabilitation facilities (IRFs) following hospitalization for hip fracture in 2009 (n=34,984). Hierarchical regression analysis showed significantly higher functional status at discharge (p<.0001) for patients with these characteristics: White or Asian; younger; female; lived alone; higher functional status at adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
4
12
1
Order By: Relevance
“…Consistent with previous studies, age of IRF hip fracture patient populations was inversely related to motor function on discharge, 25,27 while mean motor FIM on admission 25,46 and LOS were positively related to motor function on discharge. As in previous research, 25,35,28 mean motor function on discharge was poorer in IRFs with higher percentages of Black and Hispanic hip fracture patients. In this study, mean motor function was lower (p<.0001) in IRFs treating higher percentages of both Black and Hispanic patients.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies, age of IRF hip fracture patient populations was inversely related to motor function on discharge, 25,27 while mean motor FIM on admission 25,46 and LOS were positively related to motor function on discharge. As in previous research, 25,35,28 mean motor function on discharge was poorer in IRFs with higher percentages of Black and Hispanic hip fracture patients. In this study, mean motor function was lower (p<.0001) in IRFs treating higher percentages of both Black and Hispanic patients.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with previous studies indicating hip fracture patients who lived with others prior to admission had poorer self-care and mobility scores at admission. 2,10 …”
Section: Discussionmentioning
confidence: 99%
“…Andersen’s model for health services use (Figure 1) 13,14 and evidence from previous research 6,10 was used to identify variables for inclusion in this study. Andersen’s model posits that outcomes of care are influenced by factors in three domains: (1) contextual factors, including the external environment (the economic, political, and social context in which health systems operate) and facility characteristics (how the health system is structured to deliver care); (2) individual factors including predisposing (age, race, gender), enabling (social support), and need-factors (health status); and (3) healthcare access (use of IRF services).…”
Section: Methodsmentioning
confidence: 99%
“…Others have shown that social support is strongly associated with discharge destination. 7,9,17 Young and colleagues 18 also recently concluded that caregiver commitment, capacity, and preparedness are key factors in ‘long-term’ outcomes for patients with stroke following discharge from inpatient rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Social support, for example, is associated with likelihood of returning to the community. 7–9 It is unknown whether social support is similarly associated with likelihood of shorter- or longer-than-expected lengths of stay.…”
mentioning
confidence: 99%